Classical pastoral care ; v. 2 - Oden, Thomas Clark, 1931- (Grand Rapids, MI Baker, 1987)
Contents : v. 2 : Ministry through word and sacrament. Includes bibliographcial references and index.
Keywords: Clergy -- office